Understanding Frailty in Older Adults: Examining Attributes, Antecedents, and Consequences - Audai Hayajneh; Esraa Al-Nusour; Eman . Alsatari (Jordan University of Science and Technology, 2023)
Frailty has still been debated concept in the literature since thirty years ago. Conducting concept analysis contributes significantly to fully understanding the concept and paving the road to researchers to conduct their research on. The conceptual analysis of frailty in this article was guided by what is postulated by Walker and Avant (2011) textbook pertaining to concept analysis, including attributes, antecedents, consequences, and empirical referents of frailty. This analysis was elaborated based on the literature review posted in the matrix. Frailty as a multidimensional concept is more holistic in terms of addressing the psychological and social aspects, in addition to physical ones, of how older adults perceive their daily living at their later life. This analysis is a salient step in conducting further research in how frailty should be conceptually defined in the future.